Visualization and Biochemical Analyses of the Emerging Mammalian 14-3-3-Phosphoproteome - Johnson, Catherine (The American Society for Biochemistry and Molecular Biology, 2011)
Hundreds of candidate 14-3-3-binding (phospho)proteins have been reported in publications that describe one interaction at a time, as well as high-throughput 14-3-3-affinity and mass spectrometry-based studies. Here, we transcribed these data into a common format, deposited the collated data from low-throughput studies in MINT (http://mint.bio.uniroma2.it/mint), and compared the low- and high-throughput data in VisANT graphs that are easy to analyze and extend. Exploring the graphs prompted questions about technical and biological specificity, which were addressed experimentally, resulting in identification of phosphorylated 14-3-3-binding sites in the mitochondrial import sequence of the iron-sulfur cluster assembly enzyme (ISCU), cytoplasmic domains of the mitochondrial fission factor (MFF), and endoplasmic reticulum-tethered receptor expression-enhancing protein 4 (REEP4), RNA regulator SMAUG2, and cytoskeletal regulatory proteins, namely debrin-like protein (DBNL) and kinesin light chain (KLC) isoforms. Therefore, 14-3-3s undergo physiological interactions with proteins that are destined for diverse subcellular locations. Graphing and validating interactions underpins efforts to use 14-3-3-phosphoproteomics to identify mechanisms and biomarkers for signaling pathways in health and disease.